2020
DOI: 10.1002/path.5474
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis of extrahepatic cholangiocarcinoma and tumor budding

Abstract: Advances in tissue clearing and microscopy make it possible to study human diseases in three dimensions (3D). Highgrade tumor budding is known to be associated with poor prognosis in various cancers; however, little is known about the 3D architecture of tumor budding. Using tissue clearing, we analyzed the 3D structure of tumor budding and Ecadherin expression in 31 extrahepatic cholangiocarcinomas. A total of 31 thick slabs (up to 5 mm) were harvested from surgically resected tumor tissue, including 27 hilar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In recent years, tumor budding, a general clinicopathological feature of tumor aggressiveness, invasion, and poor prognosis, has attracted increasing attention. This pathologic phenomenon has also been observed in other tumors, such as extrahepatic cholangiocarcinoma (ECA) ( 2 ), pancreatic ductal carcinoma (PDC) ( 3 ), oral cancer ( 4 ), and cervical squamous cancer (ECSC) ( 5 ); thus, tumor budding is not unique to gastric cancer but is widespread among all tumors.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In recent years, tumor budding, a general clinicopathological feature of tumor aggressiveness, invasion, and poor prognosis, has attracted increasing attention. This pathologic phenomenon has also been observed in other tumors, such as extrahepatic cholangiocarcinoma (ECA) ( 2 ), pancreatic ductal carcinoma (PDC) ( 3 ), oral cancer ( 4 ), and cervical squamous cancer (ECSC) ( 5 ); thus, tumor budding is not unique to gastric cancer but is widespread among all tumors.…”
Section: Introductionmentioning
confidence: 79%
“…In 2020, Yoshizawa et al. ( 2 ) confirmed that high-grade tumor budding had more branch points than low-grade tumor budding (median, 26 vs. 20, p = 0.021) and longer mean protrusion length (median, 53.3 vs 32.1 μm, p < 0.001). Some scholars ( 10 ) have also proposed that tumor nodules within 1 mm of the tumor edge should not be regarded as tumor budding, because tumor nodules may be linked to tumor tissue in deeper sections and should be regarded as “discontinuous diffusion” of tumor tissues.…”
Section: Overviewmentioning
confidence: 99%
“…Nevertheless, the new advances in tissue clearing, antibody penetration, and microscopy offer their potential to obtain detailed 3D images of cancer tissue. For example, cleared formalin-fixed paraffin-embedded biopsy samples from pancreatic, extrahepatic, and prostate tumors were successfully cleared, obtaining detailed 3D images from the cancerous areas (van Royen et al 2016 ; Hong et al 2020 ; Yoshizawa et al 2020 ; Kolesová et al 2021 ) and a visual description of a fatty invasion from a cleared human diabetic pancreas (Tang et al 2018 ).…”
Section: Preclinical and Clinical Applications Of Optical Tissue Clea...mentioning
confidence: 99%
“…First, the connectivity of cancer cells is lost. Cancers that appear to be separate islands of neoplastic ducts embedded in stroma in 2D, are, in fact, often contiguous branching tubes of cancer cells cut in cross section (Yoshizawa et al, 2020). Second, the prevalence of a feature, such as vascular invasion, will be underestimated as focal microscopic features are unlikely to be captured in the minuscule fraction of the cancer sampled.…”
Section: Introductionmentioning
confidence: 99%